Roles of Vitamins in Immunity and COVID-19: A Literature Review - Nila Reswari Haryana; Qonita Rachmah; Mahmud Aditya Rifqi; Rian Diana; Dominikus Raditya Atmaka; Stefania Widya Setyaningtyas; Aliffah Nurria Nastiti; Asri Meidyah Agustin (Media Gizi Indonesia, 2022)
SARS-CoV-2 is a severe acute respiratory virus that causes Coronavirus Disease-19 (COVID-19). Even before the COVID-19 pandemic, diet was undeniably important in immunity. In order to be more resilient during and after the pandemic, understanding the role of vitamins is crucial. This review aims to explore the role of vitamins in supporting the immune system and its correlation to COVID-19. The article search was done using five electronic databases (i.e., Google Scholar, Semantic Scholar, ScienceDirect, PubMed, and PMC). Some of the keywords utilized in the literature search were “vitamin A and immunity” OR “vitamin B and immunity” OR “vitamin C and immunity” OR “vitamin D and immunity” OR “vitamin E and immunity”. A total of 51 articles was assessed in this literature review. Research finds vitamin A plays a role in both innate immune system cell function and humoral immunity by regulating, differentiating, and maturing immune system cells. Vitamin B complex primarily reduces inflammation by lowering serum C-reactive protein levels (CRP), while vitamin C strengthens epithelial barriers, phagocytes, T and B lymphocytes, and inflammatory mediators, to improve the immune system. Vitamin D acts as a mediator in the vitamin D receptor (VDR), an inner immune system component that regulates the humoral and adaptive immune systems through unique genetic transcriptions. Finally, vitamin E acts as an antioxidant, lowering the production of reactive oxygen and nitrogen species (ROS and RNS). In conclusion, all vitamins are essential in improving individual’s immune system that prevent from infectious diseases including COVID-19.